Portrait of a Contender: Stacey Cozart - Cozart, Stacey (Language at Work - Bridging Theory and Practice, 2010)
This summer, “Language at Work – Bridging Theory and Practice” magazine had the pleasure of speaking with Stacey Cozart, Head of the Language Services Unit within the Faculty of Arts at Aarhus University, in Aarhus, Denmark. The Language Services Unit at Aarhus University offers copy-editing services for staff and PhD students in English, translation services for administrative staff from Danish to English, and English language skills development, mainly in the form of courses in English for academic purposes.